التقييم النفسي العصبي للوظائف المعرفية لدى التلاميذ ذوي عسر الحساب - زروقي إبتسام; زدام حدة (University of Eloued جامعة الوادي, 2024)
ملخص : يهدف هذا البحث إلى تقييم الانتباه البصري كوظيفة معرفية أساسية لدى عينة من تلاميذ ذوي عسر الحساب من الصف الرابع ابتدائي، بلغ عددها 05 حالات مختارة بطريقة قصدية وتراوح سنها ما بين 9 و10 سنوات. و من أجل ذلك اعتمدنا على المنهج الوصفي، وطبقنا كل من اختبار مصفوفات رافن للذكاء، واختبار الكشف عن صعوبات التعلم المكيفESCIII-A وكذا اختبار الانتباه البصري الانتقائي الفرعي من بطارية NEPSY للإجابة على الفرضيات المطروحة. أظهرت نتائج التحليل الإحصائي اضطراب وظيفة الانتباه البصري الانتقائي لدى تلاميذ عسر الحساب، وذلك على مستوى الدقة و الزمن في الأداء على حد سواء. Abstract : This research aims to evaluate visual attention as a basic cognitive function for a sample of dyscalculia students from the fourth grade of primary school, the number of which reached 05 cases chosen in an intentional way, and their age ranged between 9 and 10 years. For this, we relied on the descriptive approach, and applied each of the Raven matrices test for intelligence, the ESCIII-A adapted learning disabilities detection test, as well as the selective visual attention subtest from the NEPSY battery to answer the hypotheses put forward. The results of the statistical analysis showed a disturbance in the function of selective visual attention of dyscalculia students, both at the level of accuracy and time in performance.
الانتباه الانتقائي البصري أنموذجا
Keywords: تقييم نفسي عصبي; وظائف معرفية; عسر الحساب; انتباه بصري انتقائي; neuropsychological assessment; cognitive functions; dyscalculia; selective visual attention